FRS2 Proteins Recruit Intracellular Signaling Pathways by Binding to Diverse Targets on Fibroblast Growth Factor and Nerve Growth Factor Receptors - Ong, S. H. (American Society for Microbiology, 2000)
The docking protein FRS2 was implicated in the transmission of extracellular signals from the fibroblast growth factor (FGF) or nerve growth factor (NGF) receptors to the Ras/mitogen-activated protein kinase signaling cascade. The two members of the FRS2 family, FRS2α and FRS2β, are structurally very similar. Each is composed of an N-terminal myristylation signal, a phosphotyrosine-binding (PTB) domain, and a C-terminal tail containing multiple binding sites for the SH2 domains of the adapter protein Grb2 and the protein tyrosine phosphatase Shp2. Here we show that the PTB domains of both the α and β isoforms of FRS2 bind directly to the FGF or NGF receptors. The PTB domains of the FRS2 proteins bind to a highly conserved sequence in the juxtamembrane region of FGFR1. While FGFR1 interacts with FRS2 constitutively, independent of ligand stimulation and tyrosine phosphorylation, NGF receptor (TrkA) binding to FRS2 is strongly dependent on receptor activation. Complex formation with TrkA is dependent on phosphorylation of Y490, a canonical PTB domain binding site that also functions as a binding site for Shc (NPXpY). Using deletion and alanine scanning mutagenesis as well as peptide competition assays, we demonstrate that the PTB domains of the FRS2 proteins specifically recognize two different primary structures in two different receptors in a phosphorylation-dependent or -independent manner. In addition, NGF-induced tyrosine phosphorylation of FRS2α is diminished in cells that overexpress a kinase-inactive mutant of FGFR1. This experiment suggests that FGFR1 may regulate signaling via NGF receptors by sequestering a common key element which both receptors utilize for transmitting their signals. The multiple interactions mediated by FRS2 appear to play an important role in target selection and in defining the specificity of several families of receptor tyrosine kinases.